2017
DOI: 10.1007/s10072-017-3192-2
|View full text |Cite
|
Sign up to set email alerts
|

MYH7 mutation associated with two phenotypes of myopathy

Abstract: The mutations of MYH7 (slow skeletal/β-cardiac myosin heavy chain) are commonly found in familial hypertrophic/dilated cardiomyopathy, and also can cause Laing early-onset distal myopathy (LDM), myosin storage myopathy (MSM), and congenital myopathy with fiber-type disproportion (CFTD). Here we report two cases whose diagnosis was hereditary myopathy according to clinical feature and muscle pathology analysis. High-throughput genomic sequencing (next generation sequencing) was performed to validate the diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
3
12
0
Order By: Relevance
“…Referring to published articles on Laing distal myopathy, common mutation types also include missense mutations, and inframe indels. The p.K1617del and p.E1508del have also been reported in a few studies [5,6,8,9,12,15,19,23,24].Besides these in-frame indels in our study, other reported mutations include p.E1687del, p.K1729del, p.E1669del, p.K1729dup, p.L1793del, p.K1784del [5,9,11,16,[26][27][28]. Therefore, in-frame deletions or duplications are common types of mutations in Laing distal myopathy.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Referring to published articles on Laing distal myopathy, common mutation types also include missense mutations, and inframe indels. The p.K1617del and p.E1508del have also been reported in a few studies [5,6,8,9,12,15,19,23,24].Besides these in-frame indels in our study, other reported mutations include p.E1687del, p.K1729del, p.E1669del, p.K1729dup, p.L1793del, p.K1784del [5,9,11,16,[26][27][28]. Therefore, in-frame deletions or duplications are common types of mutations in Laing distal myopathy.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, we have described a series of patients with genetic con rmed Laing distal myopathy. Up to now, there have been more than 30 articles on Laing distal myopathy, including three reports on Chinese patients [10][11][12]. So far, this is the largest report on Laing distal myopathy in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we have described a series of patients with genetic con rmed Laing distal myopathy. Up to now, there have been more than 30 articles on Laing distal myopathy, including three reports on Chinese patients [10][11][12]. So far, this is the largest report on…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, a number of both sporadic and familial LDM cases have been reported around the world, including several Chinese cases [10][11][12]. Here, we report three Chines LDM pedigrees and one sporadic Chinese LDM patient, and describe the clinical, radiographical, pathological and genetic features of these cases, to further expand both the genotypes and the phenotypes of LDM.…”
Section: Introductionmentioning
confidence: 86%